Construction Business Process Reengineering (CBPR): A Case Study of Construction Organizations in Malaysia - Sabki, O.W.M.; Nawi, M.N. Mohd; Mohamed, O.; Azzli, F. (Institut Teknologi Bandung, 2005)
Abstract. Business Process Reengineering (BPR) is currently one of the most popular catchwords. Companies hope to break the